Estratégias operatórias dos inspetores de Huanglongbing (Greening) de uma propriedade citrícola no interior do Estado de São Paulo - Gonçalves, Glaucia Helena (2011)
This research aimed to study the activity of the HLB's scouts, workers whose function is to identify symptomatic plants, in order to understand the physical constraints, cognitive and organizational involved in accomplishing the task, characterizing the operative approach used to identify diseased plants, and to elucidate what aspects hinder the identification of symptoms. The method adopted for the research was the Ergonomic Analysis of Work EAW (Güérin et al., 2001). The results, after validation with the operators and management, allowed understanding the complex relationships between the physical, cognitive and organizational aspects present on activity. Major difficulties were observed mainly in relation to the disposal of the scouts on the platforms and in relation to working hours, at the beginning and end of the journey. Important findings have highlighted strategies, unknown by the organization, used by scouts to locate candidates‟ trees to the fine analysis of investigation of symptoms. In conclusion, the analysis enable to understand the constraints and find technical and organizational solutions to the survey work on citrus groves as well as it showed signs and symptoms not investigated yet or rarely considered by researchers involved on searches aimed at increasing the ability to diagnose the disease in the field.